The Need of the European Public Prosecutor's Office in the Context of Strengthening the Integration - Tache Bocănială (EIRP Proceedings, 2014)
In this research we intend to have an objective analysis on the necessity of establishing within the European Union an institution with the role of tracking, investigating prosecuting criminal cases on union funds fraud. Based on the annual losses estimated to hundreds of millions of euros on which there are suspicions of fraud and the success rate of the prosecutions concerning the offenses against the EU budget, which varies considerably from one Member State to another (while the EU average is only 42.3 %), the European Commission, as the institution responsible for implementing policies and spending the EU funds proposed the establishment, starting from 1st January 2015, of the European Public Prosecutor's Office (EPPO) as union body for protecting these funds effectively and consistently in all Member States. Continuing the process of European integration requires an increased cooperation between Member States for the effective protection of the EU financial interests against fraud. Our analysis attempts to clarify to what extent the European Public Prosecutor's Office would be another step towards the completion of, along with the European Anti-Fraud Office (OLAF), Europol and Eurojust, a palette of union bodies called upon to provide the necessary protection for the proper functioning of the European Union as a whole.